ANALISIS MAKNA DENOTATIF DAN KONOTATIF PADA LIRIK LAGU “CINTA LUAR BIASA” KARYA ANDMESH - Amelia Yuliandari; Rizki Aulia; Viana Zaharani (Jurnal Bastra (Bahasa dan Sastra), 2026)
This research aims to analyze the denotative and connotativemeanings in the lyrics of the song "Extraordinary Love" byAndmash. Song lyrics are often the result of the author'simagination or experiences which are expressed throughbeautiful and harmonious words, but also contain deep hiddenmeanings. In this context, denotative meaning refers to theliteral meaning of the lyrics, while connotative meaning relatesto the associations, symbols and emotions evoked by thewords. In this research the author uses a qualitative approach in terms of semantic studies, that is why in this research theauthor focuses on the semiotic analysis of denotative andconnotative meaning in the lyrics of the song "Cinta Extraordinary" by Andmesh This analysis shows that the songlyrics not only convey an explicit message, but also contain a deeper meaning. This song describes a simple but sincere love, where true love is expressed through loyalty and sincerity, not from material symbols.